Neuropsychotherapeutics - Witkin, Jeffrey M. (Advances in pharmacology (San Diego, Calif.), 2019)
Neuropsychotherapeutics, Volume 86, the newest volume in the Advances in Pharmacology series, presents a variety of chapters from the best authors in the field, with this updated edition including sections on Pharmacotherapy of psychiatric disorders, Allosteric mechanisms for neuropsychopharmacology, Lipid rafts, Rapid-acting antidepressants, mGlu2/3 receptor antagonists, Nitric oxide: antidepressant mechanisms and inflammation, Anxiety disorders, mGlu receptors and schizophrenia, mAChR ligands for schizophrenia and addiction, PDE10 inhibitors, Obsessive-compulsive disorder, Addiction disorders (including eating), Dopamine D1 PAMs as a New Mode for Treatment of Neuropsychiatric Disorders, and more.